Enhanced simultaneous nitrification and denitrification performance in a fixed-bed system packed with PHBV/PLA blends - Sun, Haimeng; Yang, Zhongchen; Yang, Feifei; Wu, Weizhong; Wang, Jianlong (INTERNATIONAL BIODETERIORATION & BIODEGRADATION, 2020)
In the present study, simultaneous nitrification and denitrification of sewage treatment plant effluent was evaluated using an up-flow fixed-bed system packed with poly (3-hydroxybutyrate-hydroxyvalerate)/polylactide (PHBV/PLA) blends used in a dual role as carbon source and biofilms carrier. 98.1 +/- 2.9% and 87.2 +/- 6.8% of influent NH4+-N and NO3–N was removed from the synthetic wastewater. TN removal efficiency was 89.3 +/- 6.3% with the average effluent TN concentration of 1.6 +/- 0.9 mg/L during the stable period indicating that simultaneous nitrification and denitrification occurred. An initial high release of DOC in the effluent eventually stabilized at average of 9.0 +/- 3.4 mg/L. Simultaneous nitrification and denitrification occurred in the first 5 cm, and denitrification only in higher column sections. The PHBV/PLA supported system is a promising technology which could be applied for post-treatment of wastewater with low C/N ratios.